PRICING AMERICAN OPTION AS MULTI OBJECTIVE OPTIMIZATION PROBLEM WITH SPIRAL OPTIMIZATION ALGORITHM - Ramdhaina Yusuf, Lupita
American Option is one of the most option which is heavily traded in stock market. Determining the worth of option is important so that investor know how much they has to pay for the premium and estimate the profit. Early exercise facility on American Option make the holder can exercise the contract during the life of the option. This is the cause of valuation option contract for American Option is differ from European Option because we cannot use directly Black-Scholes partial differential equation. In this research, we make a modeling for pricing American Option which be seen as multi objective optimization problem. Then, we use spiral optimization algorithm to solve that multi objective optimization problem. We also want to predict the worth of option in the next period by using historical data of the option. With this approach, we get a better result for the value of the option if we compare with conventional method such as Black-Scholes differential equation and Binomial tree.